Surface contamination rates at different spatial scales in the Columbus module (ISS) during the MATISS campaigns - Lemelle, Laurence; Mottin, Eléonore; Le Tourneau, Denis; Rouquette, Sébastien; Campagnolo, Lucie; Thévenot, Cécile; Maillet, Alain; Barde, Sébastien; Garre, Emmanuel; Teisseire, Jérémie; Fontelaye, Caroline; Jousseaume, Vincent; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Future long-duration human spaceflights require developments to limit biocontamination of surface habitats. The three MATISS (Microbial Aerosol Tethering on Innovative Surfaces in the International Space Station) campaigns exposed surface treatments over several months in the ISS. To this end, eight sample holders designed were mounted with lamella-bearing FDTS ((1H, 1H, 2H, 2H)-perfluorodecyltrichlorosilane), SiOCH, and parylene hydrophobic coatings, at two different locations, for several months, during three distinct periods from 2016 to 2020. Tile scanning optical microscopy (×3 and ×30 magnifications) detected several thousand particles, indicating a relatively clean environment (a few particles per mm2). In previous studies, exposure rates were analyzed for all the coarse and fine particles detected on the largest total area of the integrated FDTS area exposed in the ISS (several cm2). Here, the contamination rates observed for a smaller constant area unit (the 0.66-cm2 window area of the holder) were statistically analyzed. Therefore, a statistical difference in rate distributions between RGSH (Return Grid Sensor House) and EDR (European Drawer Rack) and between FDTS and either SiOCH or parylene was shown for the coarse particles but not for the fine particles. The contamination rates were found to be low, confirming the efficiency of the long-term air purification system. The rates tend to vary with the astronaut occupancy rates. Surfaces of spacecraft for long-duration exploration left unmanned during dormancy periods can be considered safe from biocontamination.